Strengthening Capacities of Extension Advisory Service (EAS) Providers in making Food Systems Gender And Nutrition-sensitive: MANAGE Experiences - Kumari, Veenita; Junuthula, Shirisha (National Institute of Agricultural Extension Management, India, 2023)
Even after several decades of green revolution, malnutrition continues to be a major development challenge in most South Asian countries, and India has a major share of the malnourished population in the region. The nutritional issues in India are complex and therefore require a multifaceted, multidisciplinary solution. One facet of the solution is enriching knowledge about the causes of and solutions to malnutrition at the farm- and household-level through agricultural extension. Disseminating nutritionsensitive agricultural knowledge is not currently an activity of agricultural extension in India, but there is a great potential for integrating it through the wellestablished network of extension advisory services (EAS). This will require being carefully focused on the needs of rural communities and considering gender dimensions, that are closely linked with nutritionsensitive agriculture. In this session, we present the training approach that the National Institute of Agricultural Extension Management (MANAGE) uses for strengthening capacities of extension advisory service (EAS) providers in making food systems genderand nutrition-sensitive, and MANAGE’s experiences implementing this training in India’s extension system. We demonstrate the usefulness of the training for supporting extension agents working at the grassroots level, NGO partners in the agriculture sector, policymakers, and advocacy organizations to promote and support nutrition-sensitive agriculture among men and women farmers by making their local food basket diverse. The training is of relevance to professionals across contexts working in the agriculture sector.